Hands-On Unity 2021 Game Development - Second Edition - Borromeo, Nicolas (Packt Publishing, 2021)
Achieve mesmerizing game experiences using the latest Unity 2021 features by following a practical approach to building professional games Key Features Unleash the capabilities of C# scripting to create UIs, graphics, game AI agents and more Explore Unity's latest tools, including Universal Render Pipeline, Shader Graph, UI Toolkit, Visual Scripting, and VFX graph, to enhance graphics and animation Build an AR experience using Unity's AR Foundation Book Description Unity is a comprehensive yet simple suite of tools for developing video games. You can use Unity to not only create video games, but also AR/VR experiences, complex simulations, real-time realistic rendering, films, and practical games for training and education. With this book, you will get to grips with creating a full game from the ground up, building it step-by-step and applying your knowledge as you progress. Complete with hands-on tutorials and projects, this easy-to-follow guide will teach you how to develop the game using several Unity tools. As you advance, you will learn how to use the Unity engine, create simple scripts using C#, integrate graphics, sound, and animations, and manipulate physics to create interesting mechanics for your game. You'll be able to apply all the knowledge that you gain to a real-world game. Later chapters will show you how to code a simple AI agent to challenge the user and use profiling tools to ensure that the code runs efficiently. Finally, you'll work with Unity's AR tools to create AR experiences for 3D apps and games. By the end of this Unity book, you will have created a complete game and built a solid foundation in using a wide variety of Unity tools. What you will learn Explore both C# and Visual Scripting tools to customize various aspects of a game, such as physics, gameplay, and the UI Program rich shaders and effects using Unity's new Shader Graph and Universal Render Pipeline Implement postprocessing to improve graphics quality with full-screen effects Create rich particle systems for your Unity games from scratch using VFX Graph and Shuriken Add animations to your game using the Animator, Cinemachine, and Timeline Use the brand new UI Toolkit package to create user interfaces Implement game AI to control character behavior Who this book is for This Unity engine book is for game developers looking to migrate to the Unity game engine. If you are a developer with some exposure to Unity, this book will help you explore its latest feat ...